E-Government: Integrated, Fast, Certain and Easy Public Service Quality Management in Bali - I Putu Putra Astawa (Management and Applied Social Studies Review, 2023)
Purpose – Electronic-Based Government System is a government administration that utilizes information and communication technology to provide services to the public. The application of an electronic-based government system plays an important role in accelerating the achievement of government goals in public sector services and contributing to regional economic growth. Methodology – This study uses a quantitative descriptive research method. Researchers conducted an analysis of digital transformation in Bali in improving the quality of public services through the implementation of E-Government. An analysis of e-government seen from the perspectiveGovernment to Citizen (G2C) andGovernment to Bussiness (G2B) Findings – This research places the community as the main user of government-owned public services and the government as a service provider. The results of this study describe that e-government has an important role in improving integrated public services, among others. Improving the accessibility of public services; Improving service efficiency and effectiveness; Increase transparency and accountability; as well as increasing community participation. Originality – Originality produces new knowledge without repeating what has already been done by others.